Social tourism for families with a terminally ill parent. (September 2020) - Chung, Jin Young; Simpson, Steven
Highlights: Social tourism can benefit families with a terminally ill parent. Hidden needs and benefits of family vacation were realized due to social tourism. Social workers and oncologists play a role in facilitating social tourism.